Telemedicine in the Treatment of Viral Infections in Children - Gradinaru , Mariana; Mateescu, Silvia Aura; Rauta, Gabriele Isabela; Lepadatu, Margareta; Draganescu, Miruna Luminita (Technium BioChemMed, 2024)
Background: The COVID-19 pandemic has accelerated the adoption of telemedicine, including in paediatrics, offering a safe and effective solution for diagnosis and monitoring, particularly in the management of common viral infections in children. Telemedicine has become essential for families in remote areas, reducing the burden on traditional healthcare facilities. Aim: The study investigates the impact of telemedicine on accessibility, efficiency, and quality of treatment for paediatric viral infections, compared to traditional care. Methodology: Following the PRISMA guidelines, a systematic review was conducted on 51,900 articles published between 2020 and 2024, using databases such as PubMed, Springer, and Elsevier. Of these, 23 studies were included in the analysis, focusing on telemedicine use in diagnosis, treatment, and prevention. Results: Telemedicine improves accessibility for children in rural areas, facilitates rapid diagnosis through video consultations and connected devices, reduces costs, and enhances user satisfaction. Limitations include technological barriers, data confidentiality concerns, and legislative challenges. The integration of mobile applications and remote monitoring has significantly contributed to reducing complications and recovery time. Conclusions: Telemedicine is an effective tool in paediatrics, providing modern solutions for managing viral infections, with the potential to transform healthcare by increasing accessibility, reducing costs, and optimising clinical outcomes. Investments in infrastructure and clear regulations are crucial for maximising long-term benefits.